IMPROVE STUDENT'S CRITICAL THINKING THROUGH PROBLEM BASED LEARNING MODEL IN SOCIAL STUDIES LEARNING - riwanto, nazarius (Universitas Pendidikan Indonesia, 2019)
This research is motivated by the problem of the low critical thinking of students in social studies learning in Pasundan 2 Middle School Bandung class VII F. Based on the background of the problem the authors are interested in examining the problems faced by students. The method used in this study is Kemmis And Taggart which is in accordance with class action research (CAR). This research was conducted by applying the problem based learning (PBL) model. Before carrying out the research, the author first made an initial observation, the initial observations were made to look for the problems to be studied, initial observations carried out on Monday 18 September 2018. After the problem was found the writer immediately made a research plan. The study was conducted on Monday 25 September 2018 and ended on October 2, 2018. The number of respondents studied was 33 students. The research was conducted by applying the problem based learning model based on the results of the study showing that the success of applying the model was very good, the students were considered successful in increasing critical thinking in social studies learning.